2015
DOI: 10.1016/j.anr.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Khmer American Mothers' Knowledge about HPV and HBV Infection and Their Perceptions of Parenting: My English Speaking Daughter Knows More

Abstract: SUMMARY Purpose The purpose of this study is to explore and describe Khmer mothers’ understanding of HBV and HPV prevention as well as their perception of parenting on health and health education of their daughters in the US. Methods The qualitative pilot study guided by the revised Network Episode Model and informed by ethnographic analysis and community-based purposive sampling method were used. Face-to-face audiotaped interviews with eight Khmer mothers were conducted by bilingual female middle-aged comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Our findings further reiterate the problem reported by the IOM in 2010 (Smedley, Stith, & Nelson, ), that many Americans do not understand the health information they receive well enough to make informed decisions and act on them. Our previous studies reported lexical problems CA experience related to the lack of Khmer words for health terms (Lee et al., ,b), suggesting that health care providers need to develop culturally and linguistically relevant health communication skills, such as using culturally and linguistically competent health translators or drawings or stories to ensure that patients relate to information in ways that empower them to act on it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings further reiterate the problem reported by the IOM in 2010 (Smedley, Stith, & Nelson, ), that many Americans do not understand the health information they receive well enough to make informed decisions and act on them. Our previous studies reported lexical problems CA experience related to the lack of Khmer words for health terms (Lee et al., ,b), suggesting that health care providers need to develop culturally and linguistically relevant health communication skills, such as using culturally and linguistically competent health translators or drawings or stories to ensure that patients relate to information in ways that empower them to act on it.…”
Section: Discussionmentioning
confidence: 99%
“…A bilingual Khmer and English health survey about HPV vaccination was developed based on exhaustive literature review and qualitative data and was tested for face and content validity (Lee et al., , b). The health survey was pretested with cognitive interviews which provided formative validity through assessing item content, item styles, comprehensiveness, and responsiveness (Lee et al., , b). During the cognitive testing stage of research, we discussed whether the participants who had never heard of HPV should then skip the subsequent knowledge questions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the research evidence suggests adding an "I don't know" category in surveys during data collection, as best practice, since mothers may not comprehend specific health conditions (Lee et al, 2015).…”
Section: Information-seeking and Operationalisationmentioning
confidence: 99%
“…Recently, the importance of communication between mothers and daughters regarding HPV and cervical cancer prevention has been highlighted in light of mothers’ hesitation and lack of confidence in sharing or discussing sexual topics (Francis et al , ; Gross, Laz, Rahman, & Berenson, ; Iliyasu, Aliyu, Abubakar, & Galadanci, ; Kim & Kim, ; Lee et al , ). Mothers’ lack of information about sexual health is associated with a negative perception and a lack of discussion about sexual behavior with their daughters (Abril et al , ).…”
Section: Introductionmentioning
confidence: 99%